Drywood and Dampwood Termites - Faith M. Oi; Rudolf Scheffrahn; William Kern, Jr.; Kathleen C. Ruppert (EDIS)
Revised! ENY-211, a 6-page illustrated fact sheet by F. M. Oi, R. Scheffrahn, W. Kern, and K. C. Ruppert, describes these two groups of structurally damaging termites that live inside the wood they eat, signs of infestation, and control. Published by the UF Department of Entomology and Nematology, February 2008.